Model Pokok Bahasan Inti Deradikalisasi untuk Anak-anak Terpapar Radikalisme - Husnul Isa Harahap; Tengku Irmayani; Fuad Hasan Lubis (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2019)
Research on radicalism and deradicalization is prevalent because there are many cases of terrorism. The ideology of terrorism does not only develop among adults but also children. Children have radical ideology as a result of the ideologization process carried out by adults. When children already have this ideology, it will be easily influenced by terrorist ideology. Deradicalization is one of the ways to eliminate this radical ideology. The main question of the research is, how the model of the core subject of deradicalization for children who absorbs radical ideology? This study aims to describe the basic model of the core deradicalization program for children who have been absorbs radical ideology. The findings of this study indicate that the basic model of the core deradicalization require the contain learning about the stories of the Prophet, Rahmatan Lil 'Alamin Islam, Nationalism Insights as well as success and inspirational stories of former Islamic Boarding School students. The model can also be called the Kinila Wasbakap Model.